Pervasive and programmed nucleosome distortion on single chromatin fibres - Marty G. Yang; Hannah J. Richter; Simai Wang; Colin P. McNally; Camille M. Moore; Ali Emadi; Nicole E. Harris; Simaron Dhillon; Michela Maresca; Huimin Pan; Hayden Saunders; Ruiqiao Yang; et al. (Nature, 2026)
Abstract Despite decades of biochemical and structural studies of the nucleosome 1 , researchers lack genome-scale methods to determine variability in nucleosome structure along individual chromatin fibres. To address this, here we present Iteratively Defined Lengths of Inaccessibility (IDLI), a computational method that maps the single-molecule co-occupancy of structurally distinct nucleosomes, subnucleosomes and other protein–DNA interactions through long-read single-molecule footprinting 2,3 . IDLI classifies methylase-inaccessible footprints on individual chromatin fibres into (i) linker-histone-associated nucleosomes; (ii) nucleosomes with focal DNA accessibility along the nucleosome wrap; (iii) unwrapped nucleosomes; and (iv) subnucleosomal species such as hexasomes, tetrasomes and other short DNA protections. Applying IDLI to chromatin from mouse embryonic stem cells, we discover that more than 85% of nucleosomes exhibit intranucleosomally accessible DNA (nucleosome ‘distortion’). We observe epigenomic-domain- and expression-level-specific patterns of distortion, including at promoters and mouse satellite repeat sequences. Transcription factor (TF) motif occurrence correlates significantly with distinct types of distortion, and degron experiments provide evidence of direct regulation by TFs. We apply IDLI to in vitro endoderm differentiation in human induced pluripotent stem cells and primary mouse hepatocytes. In both cases, we observe distortion at pioneer TF FOXA2 binding sites, demonstrating that distortion is developmentally encoded and present in vivo. Finally, genetic experiments in mice show that a nucleosome-binding domain of FOXA2 directly affects nucleosome structure in vivo, implicating these protein–nucleosome interactions as direct mediators of distortion. Our work suggests extreme but regulated nucleosome structural variability at the single-molecule level. Furthermore, our approach offers opportunities to model TF binding, nucleosome remodelling and cell-type-specific chromatin regulation across biological contexts.